The Religious of education among the Ottoman Turks The role of readers and speech (model) (Journal of the College of Basic Education, 2022)
With the entry of the Ottoman Empire into the movement of history, Islam in general and religious education in particular constituted the base of its launch and the approach of its philosophy in managing the country in all its civilized aspects. Islamic law, by virtue of the religious authority that was issued by the Ottoman Sultan. The research included three sections as well as an introduction and conclusion. The first topic came to give a brief historical view of religious education in general for the Ottoman Turks and the most prominent developments that passed through this stage and the interests of the Ottoman sultans in it, while the second topic dealt with the role of readers among the Ottomans and the stages of its emergence, As for the third topic, it sheds light on the role of honorable hadith during the Ottomans and its most prominent stages